2011
DOI: 10.1177/039463201102400429
|View full text |Cite
|
Sign up to set email alerts
|

Severe Necrotizing Pneumonia Complicating Influenza A (H1N1): The Role of Immunologic Interaction

Abstract: This report describes the successful management of a documented necrotizing pneumonia due to Streptococcus pneumoniae in a child with pandemic influenza A (H1N1). The importance of early recognition of bacterial superinfection in patients with influenza and the immunologic interactive mechanisms between viruses and bacteria in determining respiratory diseases are highlighted. The role of modern molecular techniques in improving diagnostic microbiology sensitivity and informing consequent clinical care is empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We speculated that many viruses cause seasonal respiratory infections peaking in the winter months and the preceding viral illness (especially influenza) might be an important risk factor for the potentially severe NP that could follow. 6,13 Additionally, severe or very severe pneumonia has been associated with bacterial and viral coinfection in some reports. [14][15][16] This copathogenesis is characterized by complex interactions between coinfecting pathogens and the host, which lead to the disruption of physical barriers, dysregulation of immune responses, and delays in the return to homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that many viruses cause seasonal respiratory infections peaking in the winter months and the preceding viral illness (especially influenza) might be an important risk factor for the potentially severe NP that could follow. 6,13 Additionally, severe or very severe pneumonia has been associated with bacterial and viral coinfection in some reports. [14][15][16] This copathogenesis is characterized by complex interactions between coinfecting pathogens and the host, which lead to the disruption of physical barriers, dysregulation of immune responses, and delays in the return to homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe lung necrosis is more commonly developed during winter. We speculated that many viruses cause seasonal respiratory infections peaking in the winter months and the preceding viral illness (especially influenza) might be an important risk factor for the potentially severe NP that could follow 6,13 . Additionally, severe or very severe pneumonia has been associated with bacterial and viral coinfection in some reports 14–16 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study found no significant differences in age, sex, BMI, and underlying diseases among the groups; however, severe lung necrosis more commonly developed during winter. We speculated that viral infection was more likely to occur in winter and that preceding viral illness (especially influenza) might be an important risk factor for NP in childhood 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Among other causative agents, such bacteria as Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter lwoffii must also be considered in differential diagnostics [16]. In children with viral respiratory infections, in particular with recently emerged pandemic influenza A (H1N1), the interactive mechanisms between viruses and bacteria predispose to bacterial superinfections and development of necrotic pulmonary lesions [17]. In immunocompromised children, fungal infections with Candida, Aspergillus fumigatus, Cryptococcus neoformans as well as Scedosporium prolificans must be taken into account as causative agents of necrotic pneumonia [18].…”
Section: Discussionmentioning
confidence: 99%